Dysplastic Ichthyosis Uteri-like changes of the entire endometrium associated with a squamous cell carcinoma of the uterine cervix - Fadare Oluwole (BMC, 2006)
Abstract Ichthyosis uteri is an exceedingly rare condition in which the entire surface of the endometrium is replaced by stratified squamous epithelium. Originally described as an endometrial response to iatrogenically-introduced caustic substances, similar changes have since been described in association with a variety of inflammatory conditions of the endometrium. We describe herein a heretofore undescribed example of a moderately differentiated squamous cell carcinoma of the uterine cervix associated with extensive ichthyosis uteri-like changes of the entire adjacent endometrium. Additionally, the squamous epithelium of the latter also showed multifocal changes diagnostic of a low-grade squamous intraepithelial lesion. The potential genesis of this composite of findings is discussed, as is the neoplastic potential of ichthyosis uteri. It is concluded that a squamous cell carcinoma of the cervix extended proximally into the endometrium, and that there was a colonization of a pre-existing ichthyosis uteri by associated human papillomavirus. The possibility of significant cervical pathology should be considered when plaques of squamous epithelium with low grade dysplastic changes are identified in an endometrial biopsy or curettage.